DOI: 10.14264/d76168a
|View full text |Cite
|
Sign up to set email alerts
|

UQ eSpace

Abstract: The enclosed thesis details an investigation into the simulation of microcombustors with thermally orthotropic walls, using Eilmer4. The thesis details the motivational context for the work completed, then utilises this foundation to define the scope and aims of the project; the development of functional microcombustors simulations in Eilmer4. An initial review of relevant literature, predominantly relating to previous works in simulating microcombustion and heat recirculation. From the review of literature, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…I n this case the overlapping portions of R, and R , are performed together or grouped. Vince (1948) has statcd that grouping might occur when I is small because S perceives and responds to both signals together. This would lead one to expect simultaneous completion of R, and R,.…”
Section: E a C Thomasmentioning
confidence: 99%
See 1 more Smart Citation
“…I n this case the overlapping portions of R, and R , are performed together or grouped. Vince (1948) has statcd that grouping might occur when I is small because S perceives and responds to both signals together. This would lead one to expect simultaneous completion of R, and R,.…”
Section: E a C Thomasmentioning
confidence: 99%
“…T h e first, C,, is presented at time t after a warning signal, and the second, 'c2, F 2 ) , the RT to X2. It has been found that RTc2) is minimal when I is large, that this minimum is maintained as I is reduced down to some value, I $ , and that for I < I%, RTc2) is greater than the minimum (Craik, 1948;Hick, 1948; Vince, 1948). The period of length I, is called the Psychological Refractory Period.…”
mentioning
confidence: 99%